Entrepreneurship Education in The Covid-19 Pandemic: Case on Daarul Qur'an Student - Sri Mulyono (Jurnal Indonesia Sosial Sains, 2021)
This study was motivated by the Covid-19 outbreak, which hit the world in all sectors, including the school sector. The Management of Sharia Business Management Studies at the Daarul Qur'an Institute, Jakarta, as one of the religious education institutions, continues to hold Entrepreneurship Education programs while Indonesia is facing this pandemic. Thus, we can describe the learning model and business activities undertaken by students during the outbreak what strategies and approaches were used in conducting this study, namely subjective explanations. The various information instruments used were interviews and writing studies. The results showed that the entrepreneurial activities of students in the Islamic Business Management department of the Daarul Qur'an Institute included the use of their pioneering potential and complimented them, creating inventive items and cycles, adapting to the learning climate when the pandemic peaked and inspiring online interaction solutions. Another way is to protect themselves from having direct contact share with their social interactions on campus.